2008
DOI: 10.1097/mca.0b013e3282f487f3
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial hypertriglyceridemia associated with inflammatory response and procoagulant state after a high-fat meal in hypertensive patients

Abstract: Postprandial hypertriglyceridemia in hypertensive patients is associated with inflammatory response and procoagulant state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Oxidative stress is also suggested to contribute to the postprandial inflammatory response through cytokine production [65,66]. Although IL-6 concentrations were elevated after meal ingestion, this change was equal between age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is also suggested to contribute to the postprandial inflammatory response through cytokine production [65,66]. Although IL-6 concentrations were elevated after meal ingestion, this change was equal between age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 10 g of oat husk for 2 weeks has been shown to decrease PAI-1 activity without any changes in fVII (Sundell and Ranby, 1993), and Landin et al (1992) found that 10 g of guar gum administered daily for 2 weeks decreased PAI-1 activity significantly (Landin et al, 1992). Increased postprandial fVII concentrations have been linked to lipid metabolism as it increases after intake of high-fat meals (Liu et al, 2008), and it is likely that the observed reduction in fVII and PAI-1 are linked, at least in part, to the decreased triacylglycerol concentrations observed in the present study. Previous studies have shown that oat bran can reduce postprandial plasma triacylglycerol responses (Cara et al, 1992;Dubois et al, 1995), and it is likely that a decreased postprandial lipemia, if occurring repeatedly over a 2-week period, may reduce not only fasting triacylglycerol concentrations but also PAI-1 activity and fVII concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, adoption of the Western dietary pattern results in frequent episodes of relatively pronounced postprandial lipaemia, and the magnitude of this response is emerging as an independent predictor of coronary heart disease risk, although the mechanisms underpinning this association remain to be defined . The question of whether or not dietary fat intake promotes systemic inflammation in man is therefore of much current interest, particularly as many groups have reported evidence of an increase in circulating inflammatory markers shortly after ingestion of a high‐fat meal in human volunteers .…”
Section: Introductionmentioning
confidence: 99%